Peran Sinbiotik Lokal Lactobacillus plantarum Mut7 dan Tepung Ubi Jalar (Ipomoea batatas) Kaya Serat terhadap Respon Imun dan Mikrobiota Digesta : Kajian pada Tikus Sprague Dawley yang Diinfeksi dengan Salmonella typhimurium - , Lily Arsanti Lestari, STP., MP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The probiotics and prebiotics were known as an immunomodulatory agents that affect the immune function in the gastrointestinal tract (Gut Associated Lymphoid Tissue - GALT). Some probiotic strain and dietary prebiotics have been documented to enhance the gut immune responses. Objectives: To study the immunomodulatory effect of L. plantarum Mut7 and high fiber sweet potato powder. The non-specific and specific immune responses were investigated. The population of cecal microbiota and concentration of short chain fatty acid (SCFA) in the cecum were assayed. Methods: Ninety six male Sprague Dawley rats, which have the same age and body weight ranged from 200-300g, were obtained from National Agency for Drug and Food Control (NADFC), Jakarta. The rats were housed in individual cages in a room maintained at 25 â 27 oC, with 12-h light/dark cycles throughout the experimental period. The rats were adapted with AIN-93M diets for 7 days. They were divided into 2 groups (A â not infected with Salmonella typhimurium and B â infected with S. typhimurium) and each group was divided into 4 subgroups of 12 rats. The treatment for each sub groups was arranged as follow: 1) AIN-93M diets (CON)